Cultural Diversity and Cultural Distance as Choice Determinants of Migration Destination - Zhiling Wang; Thomas de Graaff; Peter Nijkamp (Tinbergen Institute, 2014)
This study analyses the impact of cultural composition on regional attractiveness from the perspective of migrant sorting behaviour. We use an attitudinal survey to quantify cultural distances between natives and immigrants in the area concerned, and estimate the migrants varying preferences for both cultural diversity and cultural distance. To account for regional unobserved heterogeneity, our econometric analysis employs artificial instrumental variables, as developed by Bayer et al. (2004). The main conclusions are twofold. On the one hand, cultural diversity increases regional attractiveness. On the other hand, average cultural distance greatly weakens regional attractiveness, even when the presence of network effect is controlled for.
Keywords: R2; Z1; 330; migration; cultural diversity; cultural distance; destination choice; sorting